Global trends and hotspots of gastrointestinal microbiome and toxicity based on bibliometrics - Duan, Jiajia; Liu, Chuanxin; Bai, Xiaoyang; Zhao, Xiaoying; Jiang, Tao (Frontiers in Microbiology, 2023)
Background: Toxicity concerns persist in the fields of public health, environmental science, and pharmacology. The intricate and vital role of the gastrointestinal microbiome in influencing toxicity and overall human health has gained increasing recognition in recent years. This study presents a comprehensive bibliometric analysis to evaluate the global scientific output, emerging trends, and research focal points in the area of gastrointestinal microbiome and toxicity. Methods: The Web of Science Core Collection database was retrieved for publications on the gastrointestinal microbiome and toxicity from 1980 to 2022. Our analysis included scholarly research papers written in English and excluded duplicate publications. We used Biblioshiny and R to summarize the count and citation metrics of included articles, and visualized research trends and keywords. CiteSpace was used to identify reference literature, keywords, and citation bursts. VOSviewer was used to visualize the network of related countries, institutions, authors, co-cited authors, and keywords. Results: A total of 2,140 articles were included, allowing us to identify significant countries, institutions, authors, and research focal points. Our results indicate a growing trend in the field, with China and the United States leading the research. The most productive journal in this area is Science of the Total Environment. Key findings revealed that research hotspots have shifted from drugs to environmental pollutants, emphasizing microplastics. Important mechanisms studied include oxidative stress, metabolism, inflammation, and apoptosis, with target organs being the gastrointestinal tract, liver, and brain. Furthermore, we highlight the rising significance of the gut-brain axis and the usage of zebrafish as a model organism. Conclusions: Despite certain limitations, such as focusing solely on English-language publications and excluding unpublished literature, our findings provide valuable insights into the current state of research on toxicity and the gastrointestinal microbiome. In the future, modifications to the gastrointestinal microbiome could offer new directions for treating and mitigating toxicity. These discoveries provide a comprehensive perspective on the broader scope of this research field.